Be an ‘Appy’ Department Chair - Roger McHaney (Academic Chairpersons Conference Proceedings, 2016)
Without a doubt, higher education has been impacted by recent technological changes. Faculty, students, and administrators are facing challenges and opportunities related to the spread of social media; the ubiquity of smart phones and tablet devices; and, the growth of wireless communications.
Keywords: Be an ‘Appy’ Department Chair